Experimental Toxemia of Chickens Contaminated with Yersinia enterocolitica Bacteria - Sotnikova, Elena D. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study is to study pathological processes dynamics at experimental infestation of chickens with Yersinia pseudotuberculosis bacteria. Materials and Methods: Bacteria were cultured on the Hottinger medium. The presence of toxins was assessed using â€œdilatation of the intestineâ€ and â€œvascular permeabilityâ€ tests. For the first test, the investigated liquid with bacteria was administered intranasally, the results were evaluated by comparing the weight difference of lungs, while for the second test the investigated liquid was administered per rectum determining after 4 h the ratio of the weight of the small intestine with the contents to body weight. For morphological studies, histological sections were stained with hematoxylin and eosin. For representative information, preparations were examined under optical microscopy â€œH604 TrinocularUnicoâ€ (USA), stereoscopic microscopy â€œBIOMED MSâ€“1 Stereoâ€ (Russia), and scanning electron microscopy â€œHitachi-800â€ with scanning add-on device (Japan). Results: At the formation of biofilms consisting of Y. pseudotuberculosis bacteria, we observed the formation of extracellular matrix, which covered the closed structures of various sizes consisting of bacterial cells, followed by subsequent formation of clusters. At the experimental toxemia of chickens, we identified in general exudative-infiltrative processes, the proliferation of antigen-primed lymphocyte, macrophage infiltration of the sinuses of the lymphoid organs, and increasing number of T-lymphocytes. At violation of the porosity in blood vessels of organs of the cardiovascular, respiratory, digestive, and excretory systems, we noted signs of hemocirculation disorders, extensive swelling, liberation of formed elements of blood and the fibrinogenation, dystrophic and necrotic processes, as well as numerous caseous necrotic foci infiltrated by leukocytes, which were revealed in the parenchymatous organs. Conclusion: When culturing Y. pseudotuberculosis bacteria, we observed the intercellular matrix and the formation of biofilms. At experimental toxemia of chickens, the pathological process dynamics was characterized by exudative and infiltrative processes, general vascular reaction, toxic myocardial dystrophy, atrophy of bursa fabricii, dystrophic, and necrotic processes in the Garder glands, Meckelâ€™s diverticulum, serous-fibrinous aerosacculitis, broken wind, signs of enterosorption, and hepatorenal syndrome